PEMBERDAYAAN TIM PENGEMBANGAN DESA WISATA DALAM PENATAAN PASAR DESA BESANG KANGIN, KELURAHAN SEMARAPURA KAJA - Kadek Windy Candrayana; Agus Kurniawan; Ni Komang Armaeni; Ketut Darma (Jurnal Abdi Daya, 2022)
Tourism has a very significant impact on economic development in a region. Tourism plays a role in accelerating the process of economic transformation in rural areas. Villagers who initially worked as farmers gradually learned to develop services to support tourism in a village. The momentum of tradition, culture and environmental exoticism can be packaged as village tourism products that attract visitors from outside the region. Efforts to increase the number of tourist villages to drive the village economy were also carried out in several villages in the Province of Bali. One of the village plans that will be developed as an ecotourism-based village is Besang Kangin Village, which is included in the administrative area of Semarapura Kaja Village. The previous year's PKM activities resulted in a jogging track master plan to attract visitors to Besang Kawan Village. As a supporting facility for tourism villages, the Besang Tourism Village Development Team plans to propose structuring traditional markets as one of the objects and places to market village community handicraft products. The problem faced in realizing this arrangement is the occurrence of floods which cause landslides in the market area, so a market arrangement design is needed that is safe from flooding and has a better appearance as a tourism object plan.